A Comparative Study of Online Digital Waqf and Blockchain-Based Digital Waqf from the Perspective of Maqāṣid al-Sharī'ah - Nur Aziz, Bayu; Dardiri, Masyhudan; Asif Misbahudin (Universitas Islam Negeri Raden Intan Lampung, 2026)
The development of digital technology has brought about significant changes in the waqf management system in Indonesia, particularly through the innovation of online digital waqf and blockchain-based waqf. This study aims to examine the comparative level of effectiveness and transparency of the two models from the perspective of maqāṣid al-syarī‘ah, particularly in the aspects of asset protection (hifẓ al-māl) and the achievement of benefits (tahqīq al-maṣlahah). The study used a qualitative method with a library research approach and a comparative analysis of scientific literature, regulations, and contemporary waqf jurisprudence concepts. The results show that blockchain-based digital waqf has advantages in terms of transparency, security, and data accountability, while online platform-based digital waqf is superior in terms of accessibility and public participation. However, the digital infrastructure for sharia-compliant waqf management, public literacy, and limitations of the continue to pose challenges for both models. From the perspective of maqāṣid al-syarī‘ah, both systems support the realization of hifẓ al-māl (protection of wealth), jalb al-maslahah (benefit), and dar’u al-mafāsid (prevention of damage) through safer, clearer, and more effective waqf management. This study emphasizes the importance of improving regulations, sharia governance, and integrating digital technology to build a contemporary waqf system that is accountable and focused on the welfare of the community.